Pengaruh Kualitas Pelayanan, Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian Di Kopi Kenangan - Kevin Afriandi Sihombing; Suryani Chodidjah (Journal of Economics, Bussiness and Management Issues, 2025)
This study aims to analyze the influence of service quality, product quality, and promotion on consumer purchase decisions at Kopi Kenangan. Using a quantitative research approach, data were collected through questionnaires distributed to 100 respondents who are regular customers in Bekasi. The sampling method applied was simple random sampling, and the collected data were analyzed using multiple linear regression tests with SPSS 25 software. The results show that partially, product quality and promotion have a positive and significant effect on purchase decisions, while service quality does not have a significant effect. This indicates that consumers tend to prioritize product attributes—such as taste consistency and beverage quality—as well as the attractiveness of promotional offers when making purchasing decisions. However, simultaneously, the three variables together have a significant influence on consumer purchase decisions. These findings highlight that product quality and promotion play a dominant role in shaping consumer behavior at Kopi Kenangan. Therefore, the company should focus on maintaining superior product standards and developing innovative promotional strategies, while continuing to uphold service quality as a supporting factor to enhance customer satisfaction and loyalty.